Pengembangan Website Informasi dan Sistem Pemesanan Menu pada Montis.yk Menggunakan Metode Waterfall - Eufemia Asmorowati; Nur Widjiyati (Pengelola Jurnal Politeknik Negeri Ketapang, 2026)
The development of information technology encourages culinary business actors to improve service quality through digital-based systems. Caffe Montis.yk still faces obstacles in presenting menu information, data management, and a payment system that is not yet optimal. The previously used website did not display complete details of the coffee composition and did not have an efficient menu management system. This study aims to develop a web-based information system for presenting information and ordering menus to improve service quality and operational efficiency. The method used is Waterfall with stages of needs analysis, system design, implementation, and testing. The system is developed using PHP, MySQL, and CodeIgniter and tested using the Black-box Testing method. The research results show that the built system is able to display complete menu information, provide an admin dashboard for data management, and has a display